Mechanics reveals the role of peristome geometry in prey capture in carnivorous pitcher plants (Nepenthes) - Moulton, D (University of Oxford, 2023)
Mathematica notebooks accompanying research article "Mechanics reveals the role of peristome geometry in prey capture in carnivorous pitcher plants (Nepenthes)"